CAPPARIS SPINOSA AND ITS HEALING PROPERTIES (ResearchJet Journal of Analysis and Inventions, 2021)
Capparis spinosa, the caper bush, also called Flinders rose, is a perennial plant that bears rounded, fleshy leaves and large white to pinkish-white flowers.The plant is best known for the edible flower buds (capers), used as a seasoning, and the fruit (caper berries), both of which are usually consumed pickled. Other species of Capparis are also picked along with C. spinosa for their buds or fruits. Other parts of Capparis plants are used in the manufacture of medicines and cosmetics.